ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PERBEDAAN PROFITABILITAS PERUSAHAAN (STUDI PADA PT TIMAH PERSERO TBK) - WAHYUNINGTYAS, INDAH (Jurnal Akuntansi AKUNESA, 2014)
This purpose of research was to determine the company’s ability to generate profitability before disclosure Corporate Social Responsibility (CSR) and after disclosure the Corporate Social Responsibility (CSR) in PT Timah (Persero) Tbk. This research uses ROA as a measure of profitability ratios. The sample uses financial statement of PT Timah (Persero) Tbk before disclosure CSR in 2001-2006 and after disclosure CSR in 2007-2012. Method data collection who used in this research is secondary data, which obtained form official website company’s. Method data analysis who used statistical test descriptive and Paired Sample T-Test. The result of Paired Sample T-Test on table Paired Samples Test give the p-value Sig.(2-tailed) of profitability is 0,42 and probability 0,05 (p-value Sig(2-tailed) < probability), it shows that Corporate Profitability have differences before and after disclosure Corporate Social Responsibility (CSR) is applied in PT Timah (Persero) Tbk. the differences of Profitability is 13,38%, which before disclosure Corporate Social Responsibility is 3,22% and after disclosure Corporate Social Responsibility is 17,01%. Keywords: Profitability, Return on Asset, CSR